Protesi metatarso-falangee - Santandrea, A.; Mercurio, D.; Giardini, P.; Cortese, F. (Lo Scalpello - Journal, 2019)
IMPLANTS FOR ARTHROPLASTY OF THE METATARSOPHALANGEAL JOINT Several techniques, from cheilectomy to arthrodesis, have been proposed for the treatment of degenerative disease of the first metatarsophalangeal joint (I MTF); each procedure presents limits and complications that have increased the interest in implant arthroplasty. Since the 1940s, numerous implants were developed for arthroplasty of the first metatarsophalangeal joint with the purpose of relieving pain and improving the degree of motion. Owing to the difficulty of reproducing the native joint and the various anatomical and mechanical stress impulses that the I MTF joint undergoes, high complication rates, unpredictable results and poor survival have been reported in the literature. We can distinguish and classify implants according to their material or design; third-generation silicone implant arthroplasty is gaining popularity. Our experience with Primus FGT double-stemmed silicone implants corroborates the results of recent retrospective studies.